Ответы и объяснения

2013-10-22T16:25:20+04:00
X^2+4x+4<4x^2-12x+9-8x+40                   x^2-x-42=0
x^2+4x+4-4x^+12x-9+8x-40                      Д=1+168=169
-3x^2+24x-45=0                                       х1=1+13:2=7
Д=576-540=36                                         х2=1-13:2=-6
x1=24+6:2=5                                            -{6;7}
x2=24-6:2=3
(-беск. ;3)(5;+беск)                              общий луч {-6;3)(5;7}

x^2-4x+4<4x^2+12x+9-8x-40                           x^2+x-42=0
x^2-4x+4-4x^2-12x-9+8x+40=0                        Д=1+168=169=13
-3x^-8x+35=0                                                 x1=-1+13:2=6
3x^2+8x-35=0                                                 x2=-1-13:2=-7
Д=64+420=484=22                                          (-7;6)
x1=-8+22;6=7/3
x2=-8-22:6=-5
(-беск.;-5][7/3;+беск.)                                       общ. луч (-7;5][7/3;6)